Microwave induced forward scattering and Luttinger liquid interferences in magnetically confined quantum wires: Carbon nanotubes, quantum wires and Luttinger liquid - Nogaret, Alain; Portal, Jean-Claude; Beere, Harvey E.; Ritchie, David A.; Phillips, Chris (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
We report on the photoresistance of a magnetic quantum wire obtained by applying a gradient of magnetic field to a two-dimensional electron gas. Electron transmission through the magnetic wire increases by an order of magnitude under microwave irradiation and exhibits frequency dependent magneto-oscillations as a function of the in plane magnetic field. Both results are fully consistent with microwave coupled Luttinger liquid edge channels which interfere at two pinning sites in the fashion of a Mach–Zehnder interferometer.